Quality of life after surgery for cerebral cavernoma: brainstem versus nonbrainstem location - Cornelius, Jan Frédérick; Hänggi, Daniel (World neurosurgery, 2016)
Objective - We sought to analyze long-term outcome and quality of life after surgery of cerebral cavernomas (CCs) with special regard to localization (brainstem vs. nonbrainstem). - Methods - We conducted a retrospective study in a tertiary care center (2000-2010). Clinical charts were analyzed. Health-related quality of life (QoL) was evaluated with the Short Form−36 questionnaire. - Results - The study included 60 patients (21 male, 39 female, mean age 39.8 years). The distribution was 67% supratentorial, 7% cerebellar, and 26% brainstem (BS). In the BS group, 87.5% had a preoperative deficit versus 18.2% in the nonbrainstem group (NBS). Operative neurologic morbidity was 31.3% for BS versus 11.4% for NBS. After mean follow-up of 43 months, neurologic status was better or the same as compared with the preoperative status in 75% of BS and all of NBS. SF-36 showed no significant differences between all cavernoma patients compared with a normative healthy population except for a better “pain” score. Subgroup analysis found the same results when comparing NBS with the normative population. Comparison of BS versus norm and NBS, respectively, showed worse scores for BS in physical but not mental health (P ≤ 0.01). - Conclusion - Clinical outcome was different depending on location: NBS recovered the same neurologic status as preoperatively and showed better QoL in physical health and lower working inability than BS. Surprisingly, there was no difference in mental health. Moreover, QoL of the operated cavernoma population after long-term follow-up did not differ from the norm. We conclude that surgery of cavernomas even in eloquent areas may result in favorable outcome and high patient satisfaction.